Kebijakan Zonasi Sekolah dan Eksklusi Administratif: Analisis Kritis terhadap Ketimpangan Akses Pendidikan di Indonesia - Ahmad Fahri Yahya Ainuri; Mirza Mahbub Wijaya (WISE Pendidikan Indonesia, 2026)
This study critically examines Indonesia’s school zoning policy as an instrument for promoting equitable access to education, with particular attention to the interaction among spatial inequality, administrative exclusion, family capacity, and educational opportunity. Employing a conceptual policy analysis through a theory-synthesis approach, the study integrates three national regulations governing new student admissions, more than 25 scientific and policy sources published primarily between 2018 and 2026, and comparative international literature on school choice, school catchment, opportunity hoarding, mobility capacity, and educational segregation. The analysis was conducted through four stages: mapping regulatory changes, categorizing empirical findings concerning formal access and institutional capacity, interpreting these findings using international theoretical perspectives, and constructing an analytical framework of bounded access. The findings demonstrate that zoning policies have expanded formal access by prioritizing geographical proximity; however, they have not automatically generated substantive educational equality because school quality, teacher distribution, infrastructure, transportation, information access, and institutional resources remain unevenly distributed. Moreover, domicile requirements, document verification, digital registration procedures, and alternative admission pathways may produce administrative exclusion, particularly among families with limited economic, social, informational, and mobility resources. This study therefore introduces the concept of bounded access to explain how formally equal admission regulations may generate unequal opportunities and educational experiences when families possess different capacities to convert formal eligibility into meaningful participation. The study implies that zoning reform should move beyond the redistribution of students and prioritize the equalization of school quality, transparent and accountable admission-data governance, administrative assistance for vulnerable families, safe and affordable mobility support, and continuous monitoring of exclusionary practices to ensure substantive educational equity.